FAKTOR-FAKTOR YANG MENGHALANG WANITA SISTEM NASAB IBU BERNIAGA SENDIRIAN DI PASAR-PASAR REMBAU NEGERI SEMBILAN - Midawati Midawati (Kafa`ah: Journal of Gender Studies, 2016)
Daily and night markets have long existed in Malaysia and Negeri Sembilan in particular. These markets are visited by matrilineal traders, China, India, Cambodia and Kelantan Malay. However, trading is not easy to be performed by women because it carries some barriers for them. Nevertheless, matrilineal women traders still dominate in number among the traders of other tribes in daily and night markets. Accordingly, this study tries to observe factors that hinder matrilineal women in performing their bussiness. The data is obtained from 91 female traders as the sample of the research by giving them questionnaires and interview. The result shows that there are six factors as the obstacles which are: culture, childhood, unsupported infrastructure, the amount of capital, less access to funding sources and safety reason.